Fuel Exports, Aid and Terrorism - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
This study employs interactive quantile regressions to assess the conditional role of foreign aid in reducing the potentially negative effect of terrorism on fuel exports in 78 developing countries for the period 1984-2008. Bilateral and multilateral aid indicators are used whereas terrorism includes: domestic, transnational, unclear and total terrorism dynamics. Interactive quantile regressions are used. The following findings are established. First, the effects of terrorism are both positive and negative across quantiles and specifications, with the impact most apparent in the highest and lowest quantiles. Second, while bilateral aid consistently decreases (increases) fuel exports at the top (bottom) quantiles, multilateral aid regularly decreases fuel exports in the top quantiles. Third, for negative thresholds in the 50th quartile and 90th decile, interaction effects between bilateral aid and terrorism dynamics are overwhelmingly not significant. Conversely, for transnational terrorism, the interaction effects between multilateral aid and terrorism dynamics significantly have negative thresholds. The hypothesis of a positive threshold is only confirmed for transnational terrorism and multilateral aid at the 90th decile. Justifications for unexpected signs and implications for fuel export policy and the management of multinational companies are discussed. This study contributes to the literature on the role of external flows in reducing the negative externalities of terrorism on development outcomes.
Keywords: F40; F23; F35; Q34; O40; 330; Exports; Foreign Aid; Terrorism; Natural Resources; Development